Postgraduate Students’ Attitude Towards the use of Digital Library Repositories for Research in Kwara State (Indonesian Journal of Multidiciplinary Research, 2023)
Digital library repositories are information resource environments, that offer accurate and reviewed information materials to users, collected from a variety of reliable sources. Studies have shown that despite the numerous benefits associated with digital library repositories, it is being underutilized. This study adopted a descriptive research design of the survey type. The sample of the study comprised 375 respondents from three universities in Kwara State, Nigeria. The research question was answered using descriptive statistics while t-test and ANOVA were used to test the hypotheses at a 0.05 level of significance. The findings of the study revealed that postgraduate students’ attitude toward the digital library repositories for research was positive; there was a significant difference between male and female postgraduate students’ attitude towards the digital library repositories for research, and there was a significant difference in postgraduate students’ attitude towards the digital library repositories for research based on institutional ownership. The study concluded that the majority of postgraduate students have a positive attitude toward digital library repositories for research. Therefore, this study recommended that postgraduate students should be encouraged to develop skills to integrate digital library repositories into their day-to-day learning activities and in conducting their research.